Language Style and Identity Shift of Mia Thermopolis: : A Representation Analysis through Stuart Hall’s Theory - nina dwi hardiana (Language Horizon: Journal of Language Studies, 2025)
The purpose of this study is to explore the relationship between language style and identity transformation through the character Mia Thermopolis in The Princess Diaries 1. This study aims to identify the type of language style, the sociolinguistic factors that influence this style and how this style affects Mia Thermopolis' identity shift. The analysis is grounded in Joos' (1967) theory of classification of language style, Janet Holmes' (2014) theory of sociolinguistic factors, and Stuart Hall's (1997) theory of representation. Using qualitative analysis, the findings reveal a progression from casual to formal language style, which affects changes in Mia's social status identity. These linguistic shifts parallel her transformation from an ordinary teenager into a royal princess, highlighting how language style functions as a marker of identity.